The Role of Ecumenical Patriarch Bartholomew in Christian Geopolitics - Tetiana Trush (International Society of Philosophy and Cosmology, 2022)
This article will deal with the role of the Ecumenical Patriarch Bartholomew in the restoration of independence of the Orthodox Church in Ukraine and a struggle with those, who do not want this independence. Nowadays we are witnessing cardinal changes in Ukraine. These changes are connected with the restoration and struggle of Ukraine for its independence both in the political arena and in the arena of the national church project. Ecumenical Patriarch Bartholomew has given invaluable help to Ukraine in this direction. Therefore, the article will highlight the way which Ukraine has come to receive Tomos. The questions, which are painful for both Ecumenical Patriarch Bartholomew and Ukraine, will be brought up. The presentation of Tomos to Ukraine is a solution of the global scale that has lasted for centuries. Tomos rises as a kind of cord against the encroachment of Russians on Ukrainian lands, church, culture. The events of 2018 at the Council of bishops of the Ecumenical Patriarchate are important from the geopolitical point of view. Patriarch Bartholomew says about the spiritual care of the Ukrainian church, confirms the status of the Constantinople Patriarchate, that the Ecumenical Patriarchate has the right to resolve conflicts of the clergy and grant the status of autocephaly and nobody else. The consequence of this was the restoration of independence of the Ukrainian Orthodox Church. In fact, Patriarch Bartholomew violated a " common opinion" which is not supported by anything that Kyiv and Ukraine are in canonical subordination to the Moscow Patriarchate. Secondly, a deep, for many century established tradition according to which Moscow and Constantinople made agreements behind Kyiv back about its destiny. All this will be discussed in this article.